Differentially regulated NADPH:cytochrome P450 oxidoreductases in parsley - Koopmann, Edda (The National Academy of Sciences of the USA, 1997)
Two NADPH:cytochrome P450 oxidoreductases (CPRs) from parsley (Petroselinum crispum) were cloned, and the complete proteins were expressed and functionally identified in yeast. The two enzymes, designated CPR1 and CPR2, are 80% identical in amino acid sequence with one another and about 75% identical with CPRs from several other plant species. The mRNA accumulation patterns for CPR1 and CPR2 in fungal elicitor-treated or UV-irradiated cultured parsley cells and in developing or infected parsley plants were compared with those for cinnamate 4-hydroxylase (C4H), one of the most abundant CPR-dependent P450 enzymes in plants. All treatments strongly induced the mRNAs for C4H and CPR1 but not for CPR2, suggesting distinct metabolic roles of CPR1 and CPR2 and a functional relationship between CPR1 and C4H.